Moaq Empire / Muhammad Zul Hafiy Zulkifli - Zulkifli, Muhammad Zul Hafiy (2020)
This case study is for ENT300, I choose Moaq Empire which they sell food product such as chocojar, cookies and cake. I believe that Moaq Empire can fulfill all the requirements in order to complete this study case. I contact the Owner of Moaq Empire, which is Mr Aqil Alif to get some information about his comackpany. From the interview, i managed to get the details about his company which is the background of the company, his profile, the company organizational structre and his company business model. So i can futher this study case after i get the informations from the owner itself and manage to complete the study case as required.